Tear film assessments for the diagnosis of dry eye. Issue 5 (October 2016) - Dohlman, Thomas H.; Ciralsky, Jessica B.; Lai, Edward C.
Abstract : Purpose of review: Dry eye disease (DED) is a complex, multifactorial condition that is challenging to diagnose and monitor clinically. To date, diagnosis has consisted largely of self-reported symptom questionnaires and a collection of clinical tests including vital dye staining, estimation of tear breakup time and Schirmer's testing, as no gold standard exists. As the dry eye field has made progress in understanding disease pathogenesis, new methods for assessment of this condition have been developed. Recent findings: DED is now known to be characterized by tear hyperosmolarity and ocular surface inflammation, and there are now commercially available devices that accurately and reliably measure tear osmolarity and matrix metalloproteinase 9, a marker of inflammation and tissue breakdown. In addition, there are a variety of imaging modalities that have shown promise in their ability to identify patients with DED by assessing tear film dimensions and tear film instability. Summary: There is a significant need for the development of tear film assessments for accurate diagnosis and monitoring of dry eye. There are a number of new devices and techniques that have shown promise in their ability help clinicians manage patients with DED.